2020
DOI: 10.1093/pubmed/fdaa096
|View full text |Cite
|
Sign up to set email alerts
|

Emerging public health challenge in UK: perception and belief on increased COVID19 death among BAME healthcare workers

Abstract: Abstract Background Coronavirus infection Disease 19 impacted every part of the world and routine life. Recent report from the Office of national statistics in UK reported disproportionate death among Black Asian and minority ethnic (BAME) population. NHS is heavily relied on the BAME work force both in front line and in the community. We attempted to explore the beliefs and perception about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 15 publications
2
59
1
1
Order By: Relevance
“… 61 However, a recent study found that lack of access to PPE was perceived by BAME HCWs in the UK as a major factor contributing to the higher death rates. 62 Recent studies suggest that in addition to being at greater risk of catching COVID-19, BAME HCWs are more likely to experience inadequate provision and reuse of PPE. 46 A BMA survey in April 2020 found that only 40% of UK BAME HCWs working in primary care felt that they had adequate PPE compared with 70% of white HCWs.…”
Section: Discussionmentioning
confidence: 99%
“… 61 However, a recent study found that lack of access to PPE was perceived by BAME HCWs in the UK as a major factor contributing to the higher death rates. 62 Recent studies suggest that in addition to being at greater risk of catching COVID-19, BAME HCWs are more likely to experience inadequate provision and reuse of PPE. 46 A BMA survey in April 2020 found that only 40% of UK BAME HCWs working in primary care felt that they had adequate PPE compared with 70% of white HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…59 However, a recent study found that lack of access to PPE was perceived by BAME HCWs in the UK as a major factor contributing to the higher death rates. 60 Recent studies suggest that in addition to being at greater risk of catching COVID-19, BAME HCWs are more likely to experience inadequate provision and reuse of PPE. 45 A BMA survey found that only 40% of UK BAME HCWs working in primary care felt they had adequate PPE compared to 70% of white HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…Such research is particularly urgent in light of the coronavirus disease 2019 (COVID-19) pandemic, which has likely exacerbated working conditions for NHS staff from Black and ethnic minority backgrounds who, as well as having to navigate greater exposure to discrimination and BHA, are particularly vulnerable to COVID-19, 33,34 work in roles with increased exposure to the disease 35 and experience disempowerment in relation to complaining about deleterious working conditions. 20 These racial and ethnic disparities need to be addressed if we are to avoid the social, economic and moral costs of excessive adverse mental health and occupational outcomes for Black, Asian and ethnic minority staff.…”
Section: Discussionmentioning
confidence: 99%